Injury mechanisms for ACL injuries in team handball - A video analysis - OIsen, O. E.; Engebretsen, L.; Mykiebust, O.; Skjoelberg, A.; Bahr, R. (Education. Physical training. Sport)
ACL injuries are very comrnon in Norvegian team handball, in particular among female players (Myklebust et al 1998). Studies based on interviews of injured players show that rnost of the injuries occur in a rnovement the players have done many times before, oflen in a faking/cutting movement or Ianding from a jump, and apparently without direct body-contact. However, observational studies of the iniury, mechanisms for ACL injuries are currently not available. The purpose ofthis study was to anaiyze the injury mechanisms for ACL injuries in fernale players based not only on player recalì, but also analysis of video-taped injury situations. Conclusion: Player interviews and video analysis both revealed two main injury mechanisms for ACL. The most usual injury mechanism, a plant & cut faking movement, occurred in every case with a forceful valgus-extemal or -internal rotation with the knee in slight flexion. Contrary to what players reported when interviewed, the movement appears to have been influenced by external forces, like a push from an opponent. The other main injury mechanism, a one-legged jump shot landing, occurred with forceful valgus-external rotation with the knee fully extended. In both the two injury mechanisms the foot was planted on the floor and in nearly all cases the foot was far outside the knee.